The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/brainsci11070933
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Environmental Predictors of Aggression in Adolescence

Abstract: This study aims to find causal factors of aggression in a group of Latino adolescents to achieve a greater understanding of human nature, taking into account personal and contextual variables. The fundamental hypothesis is that moral disengagement, personality traits, self-esteem, values, parenting, sex, and socioeconomic situation can function as possible casual factors of aggression in adolescents. The study examined the variables using the structural equations model (SEM) to determine causal factors of aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 87 publications
1
8
0
1
Order By: Relevance
“…Among the different dimensions of Big Five model, agreeableness and conscientiousness were significantly and negatively correlated with aggression. Present findings are consistent with previous studies which showed relationship of agreeableness and aggression [ 39 , 40 , 41 , 42 ]. Agreeableness, which has been defined as cooperative and understanding [ 15 ] is a characteristic that is associated to the motivation to preserve favorable interpersonal connections [ 43 ].…”
Section: Discussionsupporting
confidence: 94%
“…Among the different dimensions of Big Five model, agreeableness and conscientiousness were significantly and negatively correlated with aggression. Present findings are consistent with previous studies which showed relationship of agreeableness and aggression [ 39 , 40 , 41 , 42 ]. Agreeableness, which has been defined as cooperative and understanding [ 15 ] is a characteristic that is associated to the motivation to preserve favorable interpersonal connections [ 43 ].…”
Section: Discussionsupporting
confidence: 94%
“…The study by Robles-Haydar and colleagues [ 1 ] primarily aimed to identify the correlates of aggression in non-referred adolescents, hypothesizing a major contribution for moral disengagement in the development of antisocial tendencies. This study examined a set of clinically relevant sociodemographic, personal, and familiar variables, using structural equation models to determine causal relationships.…”
Section: Personality Traits and Socio-environmental Factors As Correl...mentioning
confidence: 99%
“…According to the available evidence, individual and interpersonal determinants play a role in the occurrence of aggressive behavior [43][44][45]. In the present study, theory of planned behavior (TPB) was selected as a framework for planning the intervention and evaluating its impact.…”
Section: Introductionmentioning
confidence: 99%